Can you net the Loch Ness Monster? : an interactive monster hunt - Terrell, Brandon, 1978-2021; Doeden, Matt (North Mankato, Minnesota : Capstone Press, a Capstone imprint, 2022)
The narrator is a dedicated monster enthusiast, and the reader must help the narrator to decide whether to pursue the Loch Ness monster, known as Nessie, or one of the other lake monsters reported in places like Lake Champlain in upstate New York, and the Congo.
Something is stirring -- Searching for Nessie -- In search of Champ -- A Congo adventure -- Explaining lake monsters.
49 choices, 21 endings--Front cover.
Includes bibliographical references (page 111) and index.
4.2
3-6
630L
S
Keywords: Loch Ness monster -- Juvenile fiction; Monsters -- Juvenile fiction; Plot-your-own stories; Loch Ness monster -- Fiction; Monsters -- Fiction; Monster fiction; Choose-your-own stories